Localization of the tight junction protein, ZO-1, is modulated by extracellular calcium and cell-cell contact in Madin-Darby canine kidney epithelial cells (The Rockefeller University Press, 1988)
Using the monoclonal antibody R26.4, we have previously identified a approximately 225-kD peripheral membrane protein, named ZO-1, that is uniquely associated with the tight junction (zonula occludens) in a variety of epithelia including the Madin-Darby canine kidney (MDCK) epithelial cell line (Stevenson, B. R., J. D. Siliciano, M. S. Mooseker, and D. A. Goodenough. 1986. J. Cell Biol. 103:755-766). In this study we have analyzed the effects of cell-cell contact and extracellular calcium on the localization and the solubility of ZO-1. In confluent monolayers under normal calcium conditions, ZO-1 immunoreactivity is found exclusively at the plasma membrane in the region of the junctional complex. If MDCK cells are maintained in spinner culture under low calcium conditions, ZO-1 is diffusely organized within the cytoplasm. After the plating of suspension cells at high cell density in medium with normal calcium concentrations, ZO-1 becomes localized to the plasma membrane at sites of cell-cell contact within 5 h in a process that is independent of de novo protein synthesis. However, if suspension cells are plated at high density in low calcium medium or if suspension cells are plated at low cell density in normal calcium growth medium, ZO-1 remains diffusely organized. ZO-1 localization also becomes diffuse in monolayers that have been established in normal calcium medium and then subsequently switched into low calcium medium. These results suggest that both extracellular calcium and cell-cell contact are necessary for normal localization of ZO-1 to the plasma membrane. An analysis of the solubility properties of ZO-1 from suspension cells and monolayers revealed that high salt, nonionic detergent, and a buffer containing chelators were somewhat more effective at solubilizing ZO-1 from suspension cells than from monolayers.